GENETICS OF CLOPIDOGREL RESISTANCE: RECENT DATA - K. B. Mirzaev; D. A. Sychev; D. A. Andreev (Российский кардиологический журнал, 2015)
Antiplatelet therapy is one of the most importance in therapy of patients with injured coronary, cerebral and peripheral arteries. The standard of acute coronary syndrome patients treatment is double antiplatelet therapy: acetylsalicylic acid with P2Y12receptor blocker. Some distinguished genetic specifics might lead to the development of resistance to antiplatelet therapy with further thrombotic complications. Current review focuses on the pharmacogenetic specifics of patients than lead clopidogrel resistance.